Model Klinik Hukum Bisnis: Pendampingan Legalitas Perusahaan dan Perancangan Kontrak Kemitraan bagi Pengusaha Orang Asli Papua - Sobardo Hamonangan; Tri Yanuaria; Dudi Mulyadi; Kristina Sawen; Ruth Kambuaya (JURNAL PENGABDIAN PAPUA, 2026)
Business activities undertaken by Indigenous Papuan entrepreneurs play an important role in supporting local economic development; however, they frequently encounter legal challenges related to business legality, licensing, and partnership agreements, which may affect the sustainability and competitiveness of their enterprises. Therefore, this community service program aimed to strengthen legal awareness and enhance the legal capacity of members of the Angsa Liar Community in Jayapura through the implementation of a Business Law Clinic model. The program was conducted from May to July 2026 at the Angsa Liar Community Secretariat, Organda Street, Padang Bulan, Jayapura City, employing participatory legal empowerment, a problem-solving approach, and clinical legal services. The methods employed included coordination meetings, legal needs assessments, legal education on business licensing and partnership agreements, practical workshops, contract drafting simulations, and individualized legal assistance. The implementation of the program resulted in a significant improvement in participants’ understanding of business legality, business registration through the Online Single Submission (OSS) system, and the preparation of legally sound partnership agreements. Furthermore, participants demonstrated the ability to identify legal issues within their businesses and prepare simple partnership contract drafts appropriate to their business activities. These findings indicate that the Business Law Clinic model provides an effective, practical, and sustainable approach to improving legal compliance and strengthening the legal capacity of Indigenous Papuan entrepreneurs. In conclusion, the program successfully enhanced participants’ legal knowledge and practical legal skills, thereby contributing to the development of legally compliant, sustainable, and competitive community-based business practices.